Factors Affecting Water Absorption Of Hydrophilic Polymeric Membrane Based On Crosslinked Empty Fruit Bunch And Polyvinyl Alcohol - Khir, Mohammad Aliff Shakir Mohamad Jamil (2018)
The hydrophilic polymeric membrane (HPM) was made up from treated empty fruit bunch (EFB) fibers impregnated with polyvinyl alcohol (PVOH) solution which contains citric acid (CTR). The production of HPM involved 3 steps which was step 1 (EFB treatment process using prehydrolysis and alkali treatment), step 2 (formation of crosslinked PVOH film), and step 3 (impregnation of treated EFB fiber with PVOH solution contains CTR). In step 1, the EFB fibers were treated by pre-hydrolysis process with 20 min, 40 min, 60 min, and 80 min, then was continue with alkali treatment process at condition 17 % NaOH, 22 % NaOH, 27 % NaOH, and 32 % NaOH. Based on the results, treated EFB fibers with 60 min prehydrolysis and 27 % NaOH alkali treatment was found as the optimum conditioned for HPM production.